2007
DOI: 10.1093/nar/gkm703
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human FOXO3a-DBD/DNA complex suggests the effects of post-translational modification

Abstract: FOXO3a is a transcription factor of the FOXO family. The FOXO proteins participate in multiple signaling pathways, and their transcriptional activity is regulated by several post-translational mechanisms, including phosphorylation, acetylation and ubiquitination. Because these post-translational modification sites are located within the C-terminal basic region of the FOXO DNA-binding domain (FOXO-DBD), it is possible that these post-translational modifications could alter the DNA-binding characteristics. To un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 53 publications
13
174
0
2
Order By: Relevance
“…In agreement, previous research has shown that FOXO1/3a acetylation at Lys-242 and Lys-245 is mediated through the antagonistic action of cAMP response elementbinding protein (CREB) and the NAD-dependent histone/lysine deacetylase sirtuins (17,39). However, the authors of these studies also predict that acetylation at Lys-242 and Lys-245 attenuates the DNA-binding activity and thereby impairs transcriptional activity of FOXO proteins (17,38,39). On the contrary, our results indicate that FOXO3a acetylation, particularly at Lys-242/5, is associated with nuclear localization, induction of downstream antiproliferative targets, cell proliferative arrest, and sensitivity to dexamethasone.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In agreement, previous research has shown that FOXO1/3a acetylation at Lys-242 and Lys-245 is mediated through the antagonistic action of cAMP response elementbinding protein (CREB) and the NAD-dependent histone/lysine deacetylase sirtuins (17,39). However, the authors of these studies also predict that acetylation at Lys-242 and Lys-245 attenuates the DNA-binding activity and thereby impairs transcriptional activity of FOXO proteins (17,38,39). On the contrary, our results indicate that FOXO3a acetylation, particularly at Lys-242/5, is associated with nuclear localization, induction of downstream antiproliferative targets, cell proliferative arrest, and sensitivity to dexamethasone.…”
Section: Discussionsupporting
confidence: 87%
“…In attempting to explore the mechanism involved, we found that the expression of CREB-binding protein (CBP) is increased, whereas SIRT1 and SIRT2 levels are suppressed by dexamethasone treatment. In agreement, previous research has shown that FOXO1/3a acetylation at Lys-242 and Lys-245 is mediated through the antagonistic action of cAMP response elementbinding protein (CREB) and the NAD-dependent histone/lysine deacetylase sirtuins (17,39). However, the authors of these studies also predict that acetylation at Lys-242 and Lys-245 attenuates the DNA-binding activity and thereby impairs transcriptional activity of FOXO proteins (17,38,39).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…6E. Of note, the mutant (581-651 aa) contains the entire transactivation domain of foxo3b, corresponding to the region 650-673 aa of human FOXO3a (45,46). Thus, these data suggest that the N-terminal of foxo3b (1-120 aa) is not required for the suppressive function of foxo3b on irf3/irf7 activity, and the C-terminal containing the transactivation domain of foxo3b (628-651 aa) is not sufficient to suppress irf3/irf7 activity.…”
Section: Foxo3b Suppresses Ifn Activation Via Irf3 and Irf7mentioning
confidence: 99%
“…Furthermore, a core FoxO3a-binding motif 5 0 -AAACA-3 0 (Tsai et al, 2007) was found in the promoter region at position À1139 to À1134 bp (FBE2) and three tandem repeats of this core motif were also observed in the region between À398 and À380 bp (FBE1), (Supplementary Figure 1). We also found several Smad-binding sites (5 0 -AGAC-3 0 ) within the CCNG2 promoter, two of which are in close proximity with FBEs.…”
Section: Ccng2 Gene Is a Transcriptional Target Of Foxo3amentioning
confidence: 99%